A kind of acrylic acid aqueous binder for lithium ion battery and preparation method thereof

Through a complex chemical preparation method, a water-based acrylic binder for lithium-ion batteries was prepared, which solved the problem of poor electrochemical performance and stability of existing binders, and achieved the chemical stability of lithium-ion batteries. and significantly improved electrochemical properties.

CN118879237BActive Publication Date: 2025-02-18广东鑫甬生物科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410906868.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-08
Publication Date
2025-02-18
Estimated Expiration
2044-07-08

AI Technical Summary

Technical Problem

The electrochemical performance and electrochemical stability of existing lithium-ion battery binders are poor, and they cannot effectively improve the defects of silicon negative electrode materials, resulting in limited commercial application of lithium-ion batteries in long-term battery life equipment.

Method used

Using a preparation method of acrylic aqueous binder for lithium-ion batteries, a series of complex chemical reactions include the reaction of carbazole with 1,3-dibromobromo-5,5-dimethylhein and perfluorohexyl The introduction of ethyl alcohol, the alkenyl group of methacryl chloride, the formation of quaternary ammonium groups of triethylenediamine and methyl iodine, and the formation of further quaternary ammonium groups of allyl bromide, and finally the formation of acrylic acid, fluorine-containing monomer, ionic monomer Polymerization prepares a binder with excellent electrochemical properties and stability.

Benefits of technology

This adhesive forms a solid three-dimensional crosslinking network structure to prevent active particles from slipping, alleviate the volume expansion of silicon negative electrode, significantly improves the chemical stability and electrochemical performance of lithium-ion batteries, and improves the overall performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004932382620000131
    Figure BDA0004932382620000131
Patent Text Reader

Abstract

The invention relates to the field of lithium ion batteries, and is used to solve the problem that the existing binder has poor electrochemical performance and electrochemical stability and cannot effectively improve the defects of silicon negative electrode materials; the molecular structure of the acrylic acid aqueous binder for lithium ion batteries contains a large number of C-F bonds, and the C-F bonds have excellent chemical stability and thermal stability, thereby improving the chemical stability of the lithium ion battery, and the molecular structure of the acrylic acid aqueous binder for lithium ion batteries also contains a large number of quaternary ammonium groups, which can improve the transmission efficiency of lithium ions, thereby improving the ionic conductivity of the electrolyte, so that the electrochemical performance of the lithium ion battery is greatly improved, and the quaternary ammonium groups can interact with anions in the electrolyte, promote the formation of an SE I film, improve the structure and performance of the SE I film, thereby improving the protective effect of the negative electrode material, reducing the penetration of the electrolyte and the loss of active substances, and further improving the chemical stability of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of lithium ion batteries, and in particular to an acrylic acid aqueous binder for lithium ion batteries and a preparation method thereof. Background Art

[0002] With the widespread application of lithium-ion batteries in electric vehicles, energy storage systems and other fields, higher requirements are placed on the energy density, cycle stability and safety of batteries. Silicon materials have become ideal negative electrode materials due to their high theoretical specific capacity. In addition, silicon is environmentally friendly, abundant in resources, has a low lithium insertion potential, and has a working voltage close to that of graphite. Therefore, it is considered to be the most promising alternative negative electrode material. However, the volume change of silicon negative electrode is large during the charging and discharging process, which can easily lead to electrode structure damage and rapid capacity decay, hindering the commercial application of silicon negative electrode in long-life equipment. In silicon negative electrode, the binder serves as a bridge between the active material and the conductive agent. It is a network that conducts electrons and ions in the electrode. It is also the key to maintaining the stability of the entire electrode morphology and mechanical properties. However, the existing binders have poor electrochemical properties and electrochemical stability, and cannot effectively improve the defects of silicon negative electrode materials. Therefore, a kind of acrylic acid water-based binder for lithium-ion batteries and its preparation method are prepared, which is of great significance for improving the overall performance of lithium-ion batteries. Summary of the invention

[0003] In order to overcome the above technical problems, the purpose of the present invention is to provide an acrylic acid aqueous binder for lithium ion batteries and a preparation method thereof, which solves the problem that the existing binder has poor electrochemical performance and electrochemical stability and cannot effectively improve the defects of silicon negative electrode materials.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A method for preparing an acrylic acid aqueous binder for lithium ion batteries comprises the following steps:

[0006] Step 1: add carbazole, 1,3-dibromo-5,5-dimethylhydantoin and acetone to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir and react for 30-40 minutes at a temperature of 25-30°C and a stirring rate of 350-450r / min, then heat to reflux and continue stirring and reacting for 4-5 hours. After the reaction is completed, cool the reaction product to room temperature, then add it to ice water, and then extract it with dichloromethane 2-3 times, combine the extracts and dry the extracts with anhydrous magnesium sulfate, then vacuum filter, and rotary evaporate the filtrate to remove the solvent to obtain intermediate 1;

[0007] Step 2: Add intermediate 1, anhydrous potassium carbonate and N,N-dimethylformamide to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 15-20 minutes at a temperature of 25-30°C and a stirring rate of 350-450r / min, then add perfluorohexylethyl alcohol and continue stirring and reacting for 15-20 minutes, then heat to 75-80°C and continue stirring and reacting for 3-4 hours, after the reaction is completed, cool the reaction product to room temperature, then vacuum filter, and rotary evaporate the filtrate to remove the solvent to obtain intermediate 2;

[0008] Step 3: Add intermediate 2, triethylamine and tetrahydrofuran to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, stir and react for 15-25 minutes at a temperature of 0-5°C and a stirring rate of 350-450r / min, then add methacryloyl chloride dropwise while stirring, and control the dropping rate to 1-2 drops / s. After the addition is completed, heat to 55-60°C and continue stirring and reacting for 5-6 hours. After the reaction is completed, cool the reaction product to room temperature, and then remove the solvent by rotary evaporation to obtain a fluorine-containing monomer;

[0009] Step 4: Add triethylenediamine, triethylamine, iodomethane and N-methylpyrrolidone to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 350-450r / min, then heat to 60-65°C and continue stirring and reacting for 20-25 hours. After the reaction is completed, cool the reaction product to room temperature, add it to ethyl acetate, let it stand and precipitate, and then vacuum filter it. Place the filter cake in a vacuum drying oven and dry it at a temperature of 60-65°C for 2-3 hours to obtain intermediate 3;

[0010] Step 5: Add intermediate 3, anhydrous potassium carbonate and N,N-dimethylformamide to a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a constant pressure dropping funnel, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 350-450r / min, then add allyl bromide dropwise while stirring, and control the dropping rate to 1-2 drops / s. After the addition is completed, the temperature is raised to reflux and the stirring reaction is continued for 6-8 hours. After the reaction is completed, the reaction product is added to a hydrochloric acid solution to precipitate, and then vacuum filtered. The filter cake is placed in a vacuum drying oven and dried at a temperature of 60-65°C for 3-4 hours to obtain an ionic monomer;

[0011] Step six: Add acrylic acid, fluorine-containing monomer, ionic monomer, potassium persulfate, sodium dodecyl sulfate, OP-10 emulsifier and deionized water into a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir the reaction at a temperature of 25-30°C and a stirring rate of 350-450r / min for 15-25min, then heat to 75-80°C and continue stirring the reaction for 6-10h. After the reaction is completed, cool the reaction product to room temperature, and then freeze-dry to obtain an acrylic acid aqueous binder for lithium-ion batteries.

[0012] As a further solution of the present invention: the dosage ratio of the carbazole, 1,3-dibromo-5,5-dimethylhydantoin and acetone in step 1 is 20 mmol:11-13 mmol:70-80 mL.

[0013] As a further scheme of the present invention: the usage ratio of the intermediate 1, anhydrous potassium carbonate, N,N-dimethylformamide and perfluorohexylethyl alcohol in step 2 is 10 mmol: 25-30 mmol: 100-120 mL: 22-24 mmol.

[0014] As a further solution of the present invention: the usage ratio of the intermediate 2, triethylamine, tetrahydrofuran and methacryloyl chloride in step three is 10 mmol: 13-15 mmol: 100-120 mL: 11-13 mmol.

[0015] As a further solution of the present invention: the dosage ratio of the triethylenediamine, triethylamine, methyl iodide and N-methylpyrrolidone in step 4 is 10 mmol: 12-15 mmol: 11-13 mmol: 40-50 mL.

[0016] As a further scheme of the present invention: the usage ratio of the intermediate 3, anhydrous potassium carbonate, N,N-dimethylformamide and allyl bromide in step five is 10 mmol: 15-20 mmol: 50-60 mL: 11-13 mmol.

[0017] As a further solution of the present invention: the mass fraction of the hydrochloric acid solution is 10-12%.

[0018] As a further solution of the present invention: the usage ratio of the acrylic acid, fluorine-containing monomer, ionic monomer, potassium persulfate, sodium lauryl sulfate, OP-10 emulsifier and deionized water in step six is ​​10-12g: 1.8-7.2g: 1.1-6.1g: 0.22-0.28g: 0.18-0.22g: 0.1-0.2g: 100-120mL.

[0019] As a further solution of the present invention: an acrylic acid aqueous binder for lithium ion batteries, the acrylic acid aqueous binder for lithium ion batteries is prepared according to the preparation method of the acrylic acid aqueous binder for lithium ion batteries.

[0020] Beneficial effects of the present invention:

[0021] The invention discloses an acrylic acid aqueous binder for lithium ion batteries and a preparation method thereof. First, carbazole and 1,3-dibromo-5,5-dimethylhydantoin are reacted, and 1,3-dibromo-5,5-dimethylhydantoin is used as a brominating agent to brominate carbazole, thereby introducing bromine atoms into carbazole to obtain an intermediate 1. Then, the intermediate 1 and perfluorohexylethyl alcohol are reacted, and the bromine atoms on the intermediate 1 react with the alcohol hydroxyl groups on the perfluorohexylethyl alcohol to introduce a large number of CF bonds to obtain an intermediate 2. Then, the intermediate 2 and methacryloyl chloride are reacted, and the NH bonds on the intermediate 2 react with the methacryloyl chloride. The acyl chloride group on the acryloyl chloride reacts to introduce an olefin group to obtain a fluorine-containing monomer, then triethylenediamine and methyl iodide react, part of the tertiary amine groups on the triethylenediamine react with the iodine atom on the methyl iodide to form part of the quaternary ammonium group to obtain intermediate 3, then intermediate 3 and allyl bromide react, the remaining tertiary amine groups on the intermediate 3 react with the bromine atom on the allyl bromide to form a quaternary ammonium group again, and an olefin group is introduced to obtain an ionic monomer, and finally a polymerization reaction is carried out with acrylic acid, fluorine-containing monomer, and ionic monomer as polymerization monomers to obtain acrylic acid aqueous solution for lithium ion batteries. The acrylic acid aqueous binder for lithium ion batteries contains a large number of carboxyl groups in its molecular structure, which can condense with the hydroxyl groups on the surface of the silicon negative electrode to form ester bonds, forming a strong three-dimensional cross-linked network structure, effectively preventing the active particles from slipping in the electrode, alleviating the volume expansion of the silicon negative electrode, and ensuring the chemical stability of the lithium ion battery. At the same time, the acrylic acid aqueous binder for lithium ion batteries also contains a large number of CF bonds in its molecular structure. The CF bonds have excellent chemical stability and thermal stability, thereby further improving the chemical stability of the lithium ion battery. In addition, the acrylic acid aqueous binder for lithium ion batteries also contains a large number of quaternary ammonium groups in its molecular structure. As the number of quaternary ammonium groups increases, their arrangement and distribution in the electrolyte become more dense. This dense distribution can form a channel-like structure. These channels provide paths for the rapid migration of lithium ions, allowing lithium ions to be transmitted more smoothly along these channels, thereby improving the transmission efficiency of lithium ions, thereby improving the ionic conductivity of the electrolyte, and greatly improving the electrochemical performance of the lithium ion battery. In addition, the quaternary ammonium groups can interact with the anions in the electrolyte to promote SE The formation of SE I film improves the structure and performance of SE I film, making SE I film more dense and uniform, thereby improving its protection effect on negative electrode materials, reducing electrolyte penetration and loss of active substances, and further improving the chemical stability of lithium-ion batteries. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Embodiment 1:

[0024] This embodiment is a method for preparing an acrylic acid aqueous binder for lithium ion batteries, comprising the following steps:

[0025] Step 1: 20 mmol carbazole, 11 mmol 1,3-dibromo-5,5-dimethylhydantoin and 70 mL acetone were added to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at 25°C and a stirring rate of 350 r / min for 30 min, and then the mixture was heated to reflux and continued to stir for 4 h. After the reaction, the reaction product was cooled to room temperature, and then added to ice water, and then extracted twice with dichloromethane, the extracts were combined and dried over anhydrous magnesium sulfate, and then vacuum filtered, and the filtrate was rotary evaporated to remove the solvent to obtain intermediate 1;

[0026] Step 2: Add 10 mmol of intermediate 1, 25 mmol of anhydrous potassium carbonate and 100 mL of N,N-dimethylformamide to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 15 min at a temperature of 25 ° C and a stirring rate of 350 r / min, then add 22 mmol of perfluorohexylethyl alcohol and continue to stir and react for 15 min, then heat to 75 ° C and continue to stir and react for 3 h, after the reaction is completed, cool the reaction product to room temperature, then vacuum filter, and rotary evaporate the filtrate to remove the solvent to obtain intermediate 2;

[0027] Step 3: Add 10 mmol of intermediate 2, 13 mmol of triethylamine and 100 mL of tetrahydrofuran to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, stir and react for 15 min at a temperature of 0°C and a stirring rate of 350 r / min, then add 11 mmol of methacryloyl chloride dropwise while stirring, and control the dropping rate to 1 drop / s. After the addition is completed, the temperature is raised to 55°C and the stirring reaction is continued for 5 h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation to obtain a fluorine-containing monomer;

[0028] Step 4: 10 mmol triethylenediamine, 12 mmol triethylamine, 11 mmol iodomethane and 40 mL N-methylpyrrolidone were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for 20 min at a temperature of 25 ° C and a stirring rate of 350 r / min, and then the temperature was raised to 60 ° C and the stirring reaction was continued for 20 h. After the reaction was completed, the reaction product was cooled to room temperature, and then added to ethyl acetate, and then allowed to stand and precipitate, and then vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at a temperature of 60 ° C for 2 h to obtain intermediate 3;

[0029] Step 5: Add 10 mmol of intermediate 3, 15 mmol of anhydrous potassium carbonate and 50 mL of N, N-dimethylformamide to a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a constant pressure dropping funnel, and stir the reaction for 20 minutes at a temperature of 25°C and a stirring rate of 350 r / min. Then, add 11 mmol of allyl bromide dropwise while stirring, and control the dropping rate to 1 drop / s. After the addition is completed, heat the mixture to reflux and continue stirring the reaction for 6 hours. After the reaction is completed, add the reaction product to a hydrochloric acid solution with a mass fraction of 10% to precipitate, and then vacuum filter. Place the filter cake in a vacuum drying oven and dry it at a temperature of 60°C for 3 hours to obtain an ionic monomer;

[0030] Step six: 10g acrylic acid, 1.8g fluorine-containing monomer, 1.1g ionic monomer, 0.22g potassium persulfate, 0.18g sodium dodecyl sulfate, 0.1g OP-10 emulsifier and 100mL deionized water are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The reaction is stirred for 15min at a temperature of 25°C and a stirring rate of 350r / min, and then the temperature is raised to 75°C and the stirring reaction is continued for 6h. After the reaction is completed, the reaction product is cooled to room temperature and then freeze-dried to obtain an acrylic acid aqueous binder for lithium-ion batteries.

[0031] Embodiment 2:

[0032] This embodiment is a method for preparing an acrylic acid aqueous binder for lithium ion batteries, comprising the following steps:

[0033] Step 1: 20 mmol carbazole, 12 mmol 1,3-dibromo-5,5-dimethylhydantoin and 75 mL acetone were added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred at 28° C. and a stirring rate of 400 r / min for 35 min, and then the mixture was heated to reflux and continued to stir for 4.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then added to ice water, and then extracted twice with dichloromethane, the extracts were combined and dried over anhydrous magnesium sulfate, and then vacuum filtered, and the filtrate was rotary evaporated to remove the solvent to obtain intermediate 1;

[0034] Step 2: Add 10 mmol of intermediate 1, 28 mmol of anhydrous potassium carbonate and 110 mL of N,N-dimethylformamide to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 18 min at a temperature of 28 ° C and a stirring rate of 400 r / min, then add 23 mmol of perfluorohexylethyl alcohol and continue to stir and react for 18 min, then heat to 78 ° C and continue to stir and react for 3.5 h, after the reaction is completed, cool the reaction product to room temperature, then vacuum filter, and rotary evaporate the filtrate to remove the solvent to obtain intermediate 2;

[0035] Step 3: Add 10 mmol of intermediate 2, 14 mmol of triethylamine and 110 mL of tetrahydrofuran to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, stir and react for 20 min at a temperature of 3°C and a stirring rate of 400 r / min, then add 12 mmol of methacryloyl chloride dropwise while stirring, and control the dropping rate to 1 drop / s. After the addition is completed, the temperature is raised to 58°C and the stirring reaction is continued for 5.5 h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation to obtain a fluorine-containing monomer;

[0036] Step 4: 10 mmol triethylenediamine, 13 mmol triethylamine, 12 mmol iodomethane and 45 mL N-methylpyrrolidone were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for 25 min at a temperature of 28 ° C and a stirring rate of 400 r / min, and then the temperature was raised to 62 ° C and the stirring reaction was continued for 22 h. After the reaction was completed, the reaction product was cooled to room temperature, and then added to ethyl acetate, and then allowed to stand and precipitate, and then vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at a temperature of 62 ° C for 2.5 h to obtain intermediate 3;

[0037] Step 5: Add 10 mmol of intermediate 3, 18 mmol of anhydrous potassium carbonate and 55 mL of N, N-dimethylformamide to a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a constant pressure dropping funnel, stir and react for 25 minutes at a temperature of 28°C and a stirring rate of 400 r / min, then add 12 mmol of allyl bromide dropwise while stirring, and control the dropping rate to 1 drop / s. After the addition is completed, the temperature is raised to reflux and the stirring reaction is continued for 7 hours. After the reaction is completed, the reaction product is added to a hydrochloric acid solution with a mass fraction of 11% to precipitate, and then vacuum filtered. The filter cake is placed in a vacuum drying oven and dried at a temperature of 62°C for 3.5 hours to obtain an ionic monomer;

[0038] Step six: 11g acrylic acid, 4.5g fluorine-containing monomer, 3.6g ionic monomer, 0.25g potassium persulfate, 0.20g sodium dodecyl sulfate, 0.15g OP-10 emulsifier and 110mL deionized water are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The mixture is stirred for 20min at a temperature of 28°C and a stirring rate of 400r / min, and then the mixture is heated to 78°C and stirred for 8h. After the reaction, the reaction product is cooled to room temperature and then freeze-dried to obtain an acrylic acid aqueous binder for lithium-ion batteries.

[0039] Embodiment 3:

[0040] This embodiment is a method for preparing an acrylic acid aqueous binder for lithium ion batteries, comprising the following steps:

[0041] Step 1: 20 mmol carbazole, 13 mmol 1,3-dibromo-5,5-dimethylhydantoin and 80 mL acetone were added to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred at 30°C and a stirring rate of 450 r / min for 40 min, and then the mixture was heated to reflux and continued to stir for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then added to ice water, and then extracted with dichloromethane for 3 times. The extracts were combined and dried over anhydrous magnesium sulfate, and then vacuum filtered. The filtrate was rotary evaporated to remove the solvent to obtain intermediate 1;

[0042] Step 2: Add 10 mmol of intermediate 1, 30 mmol of anhydrous potassium carbonate and 120 mL of N,N-dimethylformamide to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 20 min at a temperature of 30°C and a stirring rate of 450 r / min, then add 24 mmol of perfluorohexylethyl alcohol and continue stirring and reacting for 20 min, then heat to 80°C and continue stirring and reacting for 4 h, after the reaction is completed, cool the reaction product to room temperature, then vacuum filter, and rotary evaporate the filtrate to remove the solvent to obtain intermediate 2;

[0043] Step 3: Add 10 mmol of intermediate 2, 15 mmol of triethylamine and 120 mL of tetrahydrofuran to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, stir and react for 25 min at a temperature of 5 ° C and a stirring rate of 450 r / min, then add 13 mmol of methacryloyl chloride dropwise while stirring, and control the dropping rate to 2 drops / s. After the addition is completed, the temperature is raised to 60 ° C and the stirring reaction is continued for 6 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation to obtain a fluorine-containing monomer;

[0044] Step 4: 10 mmol triethylenediamine, 15 mmol triethylamine, 13 mmol iodomethane and 50 mL N-methylpyrrolidone were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for 30 min at a temperature of 30 ° C and a stirring rate of 450 r / min, and then the temperature was raised to 65 ° C and the stirring reaction was continued for 25 h. After the reaction was completed, the reaction product was cooled to room temperature, and then added to ethyl acetate, and then allowed to stand and precipitate, and then vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at a temperature of 65 ° C for 3 h to obtain intermediate 3;

[0045] Step 5: Add 10 mmol of intermediate 3, 20 mmol of anhydrous potassium carbonate and 60 mL of N, N-dimethylformamide to a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a constant pressure dropping funnel, and stir the reaction for 30 minutes at a temperature of 30°C and a stirring rate of 450 r / min. Then, add 13 mmol of allyl bromide dropwise while stirring, and control the dropping rate to 2 drops / s. After the addition is completed, the temperature is raised to reflux and the stirring reaction is continued for 8 hours. After the reaction is completed, the reaction product is added to a hydrochloric acid solution with a mass fraction of 12% to precipitate, and then vacuum filtered. The filter cake is placed in a vacuum drying oven and dried at a temperature of 65°C for 4 hours to obtain an ionic monomer;

[0046] Step six: 12g acrylic acid, 7.2g fluorine-containing monomer, 6.1g ionic monomer, 0.28g potassium persulfate, 0.22g sodium dodecyl sulfate, 0.2g OP-10 emulsifier and 120mL deionized water are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The reaction is stirred for 25min at a temperature of 30°C and a stirring rate of 450r / min, and then the temperature is raised to 80°C and the stirring reaction is continued for 10h. After the reaction is completed, the reaction product is cooled to room temperature and then freeze-dried to obtain an acrylic acid aqueous binder for lithium-ion batteries.

[0047] Comparative Example 1:

[0048] This comparative example is a method for preparing an acrylic acid aqueous binder for lithium ion batteries, comprising the following steps:

[0049] 12 g of acrylic acid, 0.28 g of potassium persulfate, 0.22 g of sodium dodecyl sulfate, 0.2 g of OP-10 emulsifier and 120 mL of deionized water were added into a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred for reaction at 30° C. and a stirring rate of 450 r / min for 25 min, and then the mixture was heated to 80° C. and the stirring reaction was continued for 10 h. After the reaction was completed, the reaction product was cooled to room temperature and then freeze-dried to obtain an acrylic acid aqueous binder for lithium ion batteries.

[0050] Comparative Example 2:

[0051] This comparative example is a method for preparing an acrylic acid aqueous binder for lithium ion batteries, comprising the following steps:

[0052] Step 1: 20 mmol carbazole, 13 mmol 1,3-dibromo-5,5-dimethylhydantoin and 80 mL acetone were added to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred at 30°C and a stirring rate of 450 r / min for 40 min, and then the mixture was heated to reflux and continued to stir for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then added to ice water, and then extracted with dichloromethane for 3 times. The extracts were combined and dried over anhydrous magnesium sulfate, and then vacuum filtered. The filtrate was rotary evaporated to remove the solvent to obtain intermediate 1;

[0053] Step 2: Add 10 mmol of intermediate 1, 30 mmol of anhydrous potassium carbonate and 120 mL of N,N-dimethylformamide to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 20 min at a temperature of 30°C and a stirring rate of 450 r / min, then add 24 mmol of perfluorohexylethyl alcohol and continue stirring and reacting for 20 min, then heat to 80°C and continue stirring and reacting for 4 h, after the reaction is completed, cool the reaction product to room temperature, then vacuum filter, and rotary evaporate the filtrate to remove the solvent to obtain intermediate 2;

[0054] Step 3: Add 10 mmol of intermediate 2, 15 mmol of triethylamine and 120 mL of tetrahydrofuran to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, stir and react for 25 min at a temperature of 5 ° C and a stirring rate of 450 r / min, then add 13 mmol of methacryloyl chloride dropwise while stirring, and control the dropping rate to 2 drops / s. After the addition is completed, the temperature is raised to 60 ° C and the stirring reaction is continued for 6 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation to obtain a fluorine-containing monomer;

[0055] Step 4: Add 12g of acrylic acid, 7.2g of fluorine-containing monomer, 0.28g of potassium persulfate, 0.22g of sodium dodecyl sulfate, 0.2g of OP-10 emulsifier and 120mL of deionized water into a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir the reaction at a temperature of 30°C and a stirring rate of 450r / min for 25min, then continue stirring the reaction at 80°C for 10h, and after the reaction is completed, cool the reaction product to room temperature, and then freeze-dry to obtain an acrylic acid aqueous binder for lithium-ion batteries.

[0056] Comparative Example 3:

[0057] This comparative example is a method for preparing an acrylic acid aqueous binder for lithium ion batteries, comprising the following steps:

[0058] Step 1: add 10 mmol triethylenediamine, 15 mmol triethylamine, 13 mmol iodomethane and 50 mL N-methylpyrrolidone into a three-necked flask equipped with a stirrer and a thermometer, stir and react for 30 min at a temperature of 30°C and a stirring rate of 450 r / min, then heat to 65°C and continue stirring and reacting for 25 h. After the reaction is completed, cool the reaction product to room temperature, add it to ethyl acetate, let it stand and precipitate, and then vacuum filter it. Place the filter cake in a vacuum drying oven and dry it at 65°C for 3 h to obtain intermediate 3;

[0059] Step 2: Add 10 mmol of intermediate 3, 20 mmol of anhydrous potassium carbonate and 60 mL of N, N-dimethylformamide to a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a constant pressure dropping funnel, and stir the reaction for 30 minutes at a temperature of 30°C and a stirring rate of 450 r / min, then add 13 mmol of allyl bromide dropwise while stirring, and control the dropping rate to 2 drops / s. After the addition is completed, the temperature is raised to reflux and the stirring reaction is continued for 8 hours. After the reaction is completed, the reaction product is added to a hydrochloric acid solution with a mass fraction of 12% to precipitate, and then vacuum filtered. The filter cake is placed in a vacuum drying oven and dried at a temperature of 65°C for 4 hours to obtain an ionic monomer;

[0060] Step 3: Add 12g of acrylic acid, 6.1g of ionic monomer, 0.28g of potassium persulfate, 0.22g of sodium dodecyl sulfate, 0.2g of OP-10 emulsifier and 120mL of deionized water into a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir and react for 25min at a temperature of 30°C and a stirring rate of 450r / min, then continue to stir and react for 10h under the condition of heating to 80°C. After the reaction, cool the reaction product to room temperature, and then freeze-dry to obtain an acrylic acid aqueous binder for lithium-ion batteries.

[0061] 100 nm silicon powder, conductive agent Super P and acrylic acid aqueous binder for lithium ion batteries from Examples 1-3 and Comparative Examples 1-3 were weighed and added into a mortar in a mass ratio of 6:2:2, and fully ground and mixed, and then deionized water was added and ground and mixed again to form a slurry with a solid content of 35%, and the slurry was coated on a copper foil current collector with a scraper, and then dried after coating, and then cut into discs with a diameter of 12 mm, and finally placed in a vacuum drying oven, and dried at a temperature of 120° C. for 12 h to obtain a silicon-based negative electrode;

[0062] The positive electrode is metallic lithium;

[0063] The electrolyte is Li PF6 dissolved in a mixed solvent of propylene carbonate and diethyl carbonate in a volume ratio of 1:4, with a molar concentration of 1 mol / L;

[0064] The separator is Celgard 2320 lithium battery separator.

[0065] The silicon-based negative electrode, positive electrode, electrolyte and separator were assembled into a CR2025 button half-cell in a glove box, and then the electrochemical performance was tested under the conditions of charge and discharge voltage window of 0.01-1.0V and current density of 0.1C, 0.2C, 0.5C, 1.0C, 2.0C and 5.0C respectively. The test results are shown in the following table:

[0066]

[0067] Referring to the data in the above table, according to the comparison between Examples 1-3 and Comparative Examples 1-3, it can be seen that the addition of fluorine-containing monomers can improve the excellent chemical stability of the acrylic acid aqueous binder for lithium-ion batteries, and the addition of ionic monomers can improve the excellent electrochemical properties of the acrylic acid aqueous binder for lithium-ion batteries. The chemical stability and electrochemical properties of the acrylic acid aqueous binder for lithium-ion batteries to which both fluorine-containing monomers and ionic monomers are added are excellent.

[0068] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0069] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing an acrylic acid aqueous binder for lithium ion batteries, characterized in that: The following steps are involved: Step 1: stirring carbazole, 1,3-dibromo-5,5-dimethylhydantoin and acetone for reaction, cooling the reaction product after the reaction is completed, then adding it into ice water, extracting it, drying the extract, vacuum filtering it, and rotary evaporating the filtrate to obtain intermediate 1; Step 2: Stir and react the intermediate 1, anhydrous potassium carbonate and N,N-dimethylformamide, then add perfluorohexylethyl alcohol and continue stirring and reacting, and after the reaction is completed, cool the reaction product, then vacuum filter, and rotary evaporate the filtrate to obtain the intermediate 2; Step 3: Stir the intermediate 2, triethylamine and tetrahydrofuran for reaction, then add methacryloyl chloride dropwise while stirring, continue stirring for reaction after the addition is complete, cool the reaction product after the reaction is complete, and then rotary evaporate to obtain a fluorine-containing monomer; Step 4: stirring triethylenediamine, triethylamine, iodomethane and N-methylpyrrolidone for reaction, cooling the reaction product after the reaction is completed, then adding it to ethyl acetate, then standing to precipitate, then vacuum filtering, and drying the filter cake to obtain intermediate 3; Step 5: Stir the intermediate 3, anhydrous potassium carbonate and N,N-dimethylformamide for reaction, then add allyl bromide dropwise while stirring, continue stirring for reaction after the addition is complete, add the reaction product to a hydrochloric acid solution after the reaction is complete, precipitate, then vacuum filter, dry the filter cake to obtain an ionic monomer; Step 6: Stir acrylic acid, fluorine-containing monomer, ionic monomer, potassium persulfate, sodium dodecyl sulfate, OP-10 emulsifier and deionized water for reaction. After the reaction is completed, cool the reaction product and then freeze-dry it to obtain an acrylic acid water-based binder for lithium-ion batteries.

2. The method for preparing an acrylic acid aqueous binder for lithium ion batteries according to claim 1, characterized in that: The dosage ratio of the carbazole, 1,3-dibromo-5,5-dimethylhydantoin and acetone in step 1 is 20 mmol: 11-13 mmol: 70-80 mL.

3. The method for preparing an acrylic acid aqueous binder for lithium ion batteries according to claim 1, characterized in that: The usage ratio of the intermediate 1, anhydrous potassium carbonate, N,N-dimethylformamide and perfluorohexylethyl alcohol in step 2 is 10 mmol: 25-30 mmol: 100-120 mL: 22-24 mmol.

4. The method for preparing an acrylic acid aqueous binder for lithium ion batteries according to claim 1, characterized in that: The usage ratio of the intermediate 2, triethylamine, tetrahydrofuran and methacryloyl chloride in step 3 is 10 mmol: 13-15 mmol: 100-120 mL: 11-13 mmol.

5. The method for preparing an acrylic acid aqueous binder for lithium ion batteries according to claim 1, characterized in that: The usage ratio of the triethylenediamine, triethylamine, methyl iodide and N-methylpyrrolidone in step 4 is 10mmol:12-15mmol:11-13mmol:40-50mL.

6. The method for preparing an acrylic acid aqueous binder for lithium ion batteries according to claim 1, characterized in that: The usage ratio of the intermediate 3, anhydrous potassium carbonate, N,N-dimethylformamide and allyl bromide in step 5 is 10mmol:15-20mmol:50-60mL:11-13mmol, and the mass fraction of the hydrochloric acid solution is 10-12%.

7. The method for preparing an acrylic acid aqueous binder for lithium ion batteries according to claim 1, characterized in that: The usage ratio of the acrylic acid, fluorine-containing monomer, ionic monomer, potassium persulfate, sodium dodecyl sulfate, OP-10 emulsifier and deionized water in step six is ​​10-12g: 1.8-7.2g: 1.1-6.1g: 0.22-0.28g: 0.18-0.22g: 0.1-0.2g: 100-120mL.

8. An acrylic acid aqueous binder for lithium ion batteries, characterized in that: The acrylic acid aqueous binder for lithium ion batteries is prepared according to the preparation method of the acrylic acid aqueous binder for lithium ion batteries according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method for preparing antisymmetric N,Ní»-1-4-dialkyl triethylene diammonium tetrafluoroborate

    CN101307053A

  • Method for synthesizing 1-bromocarbazole by taking carbazole as raw material

    CN113582910A